Lung cancer - statistical analysis data from 2016 to 2019 in Shtip, Republic of North Macedonia (International Journal of Scientific Research and Management (IJSRM), 2021)
According to the data of the World Health Organization, globally, in 2018, 18 million new cases of cancer were registered, of which 2.09 million (11.6%) were diagnosed with lung cancer and 9.6 million deaths, of which 1.76 million (18.4) are in lung cancer. The overall standardized incidence rate by age is 25% higher in men than in women. Statistical data taken from the Center for public health – Shtip, shows that lung cancer is more common in men and more common in people aged 55-65, while in women there is no dominance of a certain age group. The total number of newly registered cases of lung cancer in Stip for 2016 is a total of 25. In 2017 the total number is 35 of which 30 of the patients are men, most of them are aged 55 to 65 years. In 2018 the total number is 22. The total number of newly registered cases of lung cancer in Shtip for 2019 is 7 of which are all registered in men, most are aged 45 to 54 and 65 to 75 years. Due to the frequency of this type of cancer, it is important to raise the awareness in people to prevent or detect the disease early, which improves the chances for a better prognosis and a better outcome of treatment.